2016
DOI: 10.1007/s00266-016-0651-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Resident Participation in Outpatient Plastic Surgical Procedures

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Those studies have found that there was no difference in overall outcomes in surgical cases performed with or without the use of residents. 9,[28][29][30][31][32][33][34][35] Thus far, the data support comparable outcomes and efficiency between cases which do not involve trainees and cases involving trainees. 26,35 The operating room is one of the costliest aspects of health care; therefore, maximizing utilization through overlapping or simultaneous operations allows for improvements in the delivery of cost-effective and timely care.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Those studies have found that there was no difference in overall outcomes in surgical cases performed with or without the use of residents. 9,[28][29][30][31][32][33][34][35] Thus far, the data support comparable outcomes and efficiency between cases which do not involve trainees and cases involving trainees. 26,35 The operating room is one of the costliest aspects of health care; therefore, maximizing utilization through overlapping or simultaneous operations allows for improvements in the delivery of cost-effective and timely care.…”
Section: Discussionmentioning
confidence: 63%
“…To determine if resident involvement affected complication rates, there have been several investigations on the impact of resident involvement in surgical operations. Those studies have found that there was no difference in overall outcomes in surgical cases performed with or without the use of residents 9,28–35 . Thus far, the data support comparable outcomes and efficiency between cases which do not involve trainees and cases involving trainees 26,35 …”
Section: Discussionmentioning
confidence: 90%
“…[1][2][3][4][5][6][7][8][9][10] Given these considerations, it remains paramount to understand the perspective of attending surgeons who must balance commitments to teach residents in surgical cases while optimizing clinical productivity to maintain revenue. [11][12][13][14] Up to date, studies on complications and re-admissions associated with resident involvement have not established a clear pattern. [1][2][3][4][5][6][7][8][9][10] Furthermore, the increasing pressures to maximize clinical productivity, paired with the shift towards bundled payment models and value-based care, may dis-incentivize resident involvement in the operating room thus weakening the mission of academic medicine.…”
mentioning
confidence: 99%
“…For several surgical specialties, data has shown an increase in operative time, length of stay, and overall cost associated with resident participation in such cases 1–10 . Given these considerations, it remains paramount to understand the perspective of attending surgeons who must balance commitments to teach residents in surgical cases while optimizing clinical productivity to maintain revenue 11–14 . Up to date, studies on complications and re-admissions associated with resident involvement have not established a clear pattern 1–10 .…”
mentioning
confidence: 99%
“…A few studies, however, showed increased overall morbidity rate in various general surgery procedures [9,14]. Interestingly, several of the studies showed that trainee participation did not negatively impact morbidity or mortality and deemed that resident participation is overall safe for surgical patients [14][15][16].…”
mentioning
confidence: 99%